A colour active contour model for contour extraction in natural scenes - Ngoi, Kian Peng (2010)
The performance of active contours, originally introduced as snakes, depends on the proper selection of model parameters and initial contours. In natural scenes, active contours often fail to converge to the desired solution because of unconstrained environmental conditions and complex object shapes. This thesis presents a new colour active contour model for contour extraction in natural scenes. The proposed model is able to extract complex object boundaries in natural scenes without the need to re-tune model parameters and image thresholds. Specific object features and a priori knowledge of object topology are not required.